Intermittent water supply : a South African perspective - Loubser, Carlo; Chimbanga, Bubala Mwiinga; Jacobs, Heinz Erasmus (Water S. A., 2021)
The prevalence of intermittent water supply in South Africa was investigated in this research study. Data on intermittent water supply in South Africa was collated by considering the following four sources: a targeted water services provider survey; published databases and related reports; open-access publications, such as online media articles; and field visits by the project team to selected areas. The data were spatially and temporally analysed to determine the prevalence of intermittent water supply. The population afected by intermittent water supply increased by ~26% between 2008 and 2017, which exceeds the population increase of ~12% over the same period. Moreover, 22 million people in South Africa were afected by intermittent water supply in 2017. Results from this study confirm an increased prevalence of intermittent water supply over time and show that 65 of the 231 municipalities in South Africa supplied water intermittently, 32 had continuous water supply and 134 had no data. Fundamentally, the outcomes highlight the widespread occurrence of intermittent water supply in South Africa, which is in line with the poor state of water services delivery in South Africa, as portrayed in the 2018 National Water and Sanitation Master Plan by the national Department of Water and Sanitation.